(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The research aims to shed light on the obstacles that hinder the use of taxpayers’ commercial books covered by provisions of the amended commercial book-keeping system No. 2 of 1985 and ways to address these obstacles. On this basis, the main null hypothesis was formulated that there is no statistically significant relationship between the obstacles to the adoption of the commercial books and taxable income. The research data were collected on the base of three applied case studies of registered taxpayers in the General Commission of Taxes, GCT, together with the use of a questionnaire distributed to a sample of taxpayers ( companies ). The collected data were analyzed, the result were presented and the hypothesis was tested using the Statistical Package for the Social Sciences, SPSS. The research results led to rejecting the research main null hypothesis and accepting the alternative hypothesis that there is a statistically significant relationship between the adoption of the obstacles and the taxable income. The search also reached a number of important conclusions that the tax authority does not rely on the taxpayers’ commercial books , despite their objective and formal conditions , and it adopted annual controls in determining their taxable incomes in an inaccurate and subjective manner that makes taxpayers do not care any importance to their commercial books.